Simulation and financial assessment of three types of solar energy for the generation of steam. (2021)
In this article three types of alternative energies were evaluated, which are High Concentration Photovoltaic PV, Concentrated Solar Power - Direct Linear Fresnel Steam and Stirling Dish, in a Colombian field called TECA field which is located in Puerto Nare, Antioquia, to generate steam and supply it.